Penggunaan model problem based learning untuk meningkatkan berfikir krearif siswa kelas IV sekolah dasar - Handayani, Putri; Anugrah Ramadhan Firdaus; Cucun Sutinah (IKIP Siliwangi, 2024)
This study aims to determine the improvement of creative thinking of fourth grade students, students' responses to creative thinking skills and teacher constraints in implementing the problem-based learning model. Increasing creative thinking is one of the core competencies in skills that cannot be separated from the 21st century competencies that students must have. This research uses mixed methods with the explanatory sequential design. Research subjects in improving creative thinking in fourth grade elementary school students. The determination of the subject was selected from the results of interviews in the field of one of the elementary schools in West Bandung Regency as many as 26 students. Qualitative data collection techniques by giving pretests and posttests followed by quantitative data collection in the form of student response questionnaires, teacher observations and teacher interviews. The results showed that, the field trial of the use of problem-based learning models to improve creative thinking was included in the good and improved categories. Thus, the use of this problem-based learning model can be used in the learning process to improve the creative thinking of fourth grade elementary school students.